Jovens da Escola de Ensino Médio Wladimir Roriz: construção da cultura de paz e dos valores humanos - Carneiro, Maria Joyce Maia Costa (2014)
This research was conducted for two years (2011/2012), with the young students, the High School Wladimir Roriz (EEMWR), it happened to building a Culture of Peace and Human Values, as valuable moments of sharing and solidarity in the process, I have followed the development of “Living Values Education program” (LIVE), whose goal is to bring the school community, especially young people, to reflect human values through attitudes in the school environment that fosters a culture So the Peace, by monitoring the LIVE IN EEMWR was possible to see how the young students of the same were related to this Program. The methodology used was configured in participatory research (BRANDÃO, 1984; LE BOTERFE, 1985; LAKATOS; MARCONI, 2004; SEVERINO, 2002), whose main phases: 1) conducting four (4) meetings inspired the Culture Circles (CC) of Paulo Freire with fifteen (15) students from LIVE to share experiences from the learning of human values in order to build a Culture of Peace in the school context. In addition, a focus group session with eight (8) among students attending the LIVE was held; 2) two (2) seminars to raise awareness and presentation of the Doctoral Study Plan 32 (thirty two) teachers and four (4) school managers. The second meeting was held to return in order to expose the results of research; 3) review of literature on the topic; 4) documentary analysis of key materials that support the VIVE and Policy Project (PPP); 5) conducting semi-structured interviews with twelve (12) teachers from among those who were present at the seminar, eight (8) students, five (5) parents, three (3) managers EEMWR to capture their perceptions regarding LIVE; 6) conducting two (2) semi-structured interviews, one with the coordinator of LIVE and another with director of the 9th Regional Coordinator for Education Development (CREDE); 7) conducting a semi-structured interview with the coordinator of the Generation of Peace Programme in Department of Education (SEDUC); 8) An unstructured interview with three (3) managers LIVE on the challenges of school. The research process was important because participants enter me as a researcher in the everyday, in order to sensitize the school community about the need to address the issue of Human Values, presented by LIVE on related teaching and learning activities. The results are: a) young people are open to new experiences and live feel happy when you opportunities to experience positive human values such as peace, friendship, love, solidarity and unity are given; b) teachers also understand that LIVE has excellent purposes, and needs to be strengthened, not only in school but in society as a whole; c) Manager Core school fully supports the initiative and offers strategic contributions to its development; d) parents do not participate, mainly due to the distance between the place they live and the school; e) there are difficulties pointed out by the students with regard to physical spaces for performing activities that require concentration , such as reading, testing plays, meetings etc. However, the experience of human values that oppose the inhuman logic of capitalism, it is still difficult to be consolidated because society in general is becoming increasingly emptied of positive feelings when investing in competitiveness without limits. The results also indicate that: students understand their role in the scenario of building a Culture of Peace and solicit greater presence of teachers who are not yet involved with LIVE. Certainly, LIVE represents a new ideal of human existence, making believe that another world is possible. One could therefore dream of a world of peace? Not only dream but to build it as it is necessary to peace could smile, in order to live, to be able.